A confirmation of the indirect impact of sugarcane on deforestation in the Amazon. Issue 2 (4th May 2017) - Jusys, Tomas
ABSTRACT: A widely discussed assumption that the expansion of sugarcane indirectly contributes to deforestation in Brazil has been backed statistically by only a handful of studies. The present research measures the indirect effect of sugarcane in Brazil's frontier counties as a weighted summation of changes in sugarcane area in agricultural (non-frontier) counties, where weights are constructed using road distances and the bandwidth that minimizes overall model error. In addition to economic variables, indirect effect variables are employed to create a model that explains deforestation. Parameters are estimated following fixed-effects methodology. The results reveal that sugarcane indirectly contributed to deforestation in Brazil during the period from 2002 to 2012. The effect was estimated to be sizeable; in particular, 16.3 thousand km 2 of forest was cut by economic actors displaced by expanding sugarcane plantations. This figure constitutes 12.2% of deforestation in Brazil from 2002 to 2012 and is equivalent to 189.4 million Mg of carbon emissions.